The Measurement of Volume and Surface Area of the Middle Ear Pneumatic System and Its Clinical Significance - Wendi Zhang; Xu Bie; Shen Yu (Journal of Otology, 2025)
Background The middle ear pneumatic system (MEPS) supports pressure balance, essential for sound conduction. Its volume and surface area are key indicators of pneumatization and ventilation, yet their specific contributions to pressure regulation need further exploration.Objective To evaluate the accuracy and sensitivity of parameters characterizing the MEPS, including volume (V), surface area (S), and surface-area-to-volume ratio (S/V), in normal ears.Materials and Methods We collected CT images of the temporal bone from 63 normal ears for this study. The volume(V), surface area(S), and surface-area-to-volume ratio(S/V) of the MEPS were measured and calculated using three-dimensional reconstruction technology. Statistical methods were used to process the data and determine the 95% reference range for the S, V, and S/V of the MEPS in the normal ear. At the same time, we analyzed the impact of differences in gender and the left and right sides on the measurements.Results The 95% reference values for the S, V, and S/V of the MEPS in normal ears were 1057.10 ~ 18239.16 mm², 609.16 ~ 9854.11 mm3, and 1.39 ~ 2.52 mm-1 respectively. There were no significant differences in the measurements between genders and between the left and right sides.Conclusions and Significance This study has established the 95% reference values for the S, V, and S/V of the MEPS in normal ears, which were 1057.10-18239.16 mm², 609.16-9854.11 mm3, and 1.39-2.52 mm-1 respectively. We found that while there is a wide variation in the V values among normal ears, there is less variability in the S/V values. This structural characteristic suggests that changes in the S/V value may have a more significant impact on the balance of middle ear pressure, and it provides important reference data for the construction and functional reconstruction of three-dimensional models of the MEPS. These findings may aid in diagnosing middle ear disorders, such as otitis media with effusion, and guide interventions to restore pressure balance.